Experimental and numerical investigations of concrete-filled stainless steel tube stub columns under axial partial compression - He, An (2021)
This paper presents a thorough experimental and numerical investigation into the structural performance and load-carrying capacities of circular concrete-filled stainless steel tube (CFSST) stub columns under axial partial compression. The experimental programme was carried out on 3 fully loaded (reference) circular CFSST stub column specimens and 15 partially loaded circular CFSST stub column specimens, with a series of material and geometric parameters (including the concrete grade, the stainless steel tube size and the area and shape of the partial compression region) varied. Analysis of the obtained test results revealed that the partial compression area ratio, defined as the ratio of the concrete gross area to the partially loaded area, and the confinement factor, given as the steel tube to concrete plastic compression resistance ratio, are the two key factors influencing the structural behaviour and load-carrying capacities of circular CFSST stub columns subjected to partial compression. The testing investigation was supplemented by a systematic finite element (FE) modelling study, where the numerical models were firstly developed and validated against the experimentally derived results and then employed to conduct parametric studies for the purpose of expanding the experimental data pool over a broader range of partial compression area ratios and confinement factors. In the absence of the established codified design provisions for CFSST stub columns subjected to partial compression, the corresponding design rules for partially loaded concrete-filled carbon steel tube stub columns, as given in the European code and American specification, were evaluated for CFSST stub columns under partial compression load, and shown to result in both conservative and scattered resistance predictions. Other recently developed proposals for partially loaded concrete-filled carbon steel tube stub columns were also assessed for CFSST stub columns, indicating a high level of design accuracy on average but with many unsafe resistance predictions. Finally, a new design approach was developed specifically for CFSST stub columns under partial compression, and shown to yield precise, consistent and safe-sided resistance predictions through comparing against the test and FE results.